PENGARUH BRAND TRUST DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SKINTIFIC (STUDI KASUS PADA FOLLOWERS INSTAGRAM @SKINTIFICID) - Ayu Wulandari, Diah; Arintowati, Dyan; Tri Mahendra , Prasetya (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study is a quantitative study using brand trust and price variables as independent variables, while purchasing decisions are dependent variables. Data collection techniques by distributing questionnaires given to 400 respondents who are skintific Instagram followers. Respondents were selected using the non-probability sampling method. The data analysis method uses multiple linear regression analysis and hypothesis testing. From the results of this study, it can be concluded that brand trust and price, both partially and simultaneously, have a positive and significant effect on purchasing decisions. It is hoped that companies can build consumer trust and set prices that are in accordance with product quality. This can support consumers in making repeat purchases of products offered by skintific.